Ureter Quadruplication with Huge Ureteral Cyst - Joshi, R; Singh, DR (Journal of Nepal Paediatric Society, 2015)
Ureteral quadruplication is an extremely rare congenital anomaly. It was first reported in 1975. The patients may present with different features and complications in respect to this congenital anomaly. They may also present with other congenital anomalies. Diagnosis sometimes is difficult and may need to be investigated with Magnetic Resonance Urogram, CT scan apart from routine investigations like ultrasonography and intravenous urogram. Surgical treatment should be based on the operative and investigational finding. We present the twelfth reported case but the first from Nepal. It was associated with a large ureteral cyst with diagnostic dilemma. Surgical exploration was done with a provisional diagnosis of large retroperitoneal cyst. J Nepal Paediatr Soc 2015;35(1):79-81